Giant ovarian cyst - Santos, Vitorino M.; Santos, Lister A. M.; Modesto, Fabiana R. D. (BALI MEDICAL JOURNAL, 2015)
We read the exceedingly rare case study recently described by Hota et al. about giant ovarian cyst in term pregnancy1. The patient was a 25-year-old woman undergoing therapy for hypothyroidism, with history of three previous deliveries (P1L1A1). USG of abdomen and pelvis was normal with respect to gestational age in the second trimester, and ovarian cyst was not seen. However, the USG of control done on the third trimester revealed a left ovarian cyst (21x18 cm), with normal obstetric features. The weight of removed cyst of 29x20 cm was 4.9 kg, and the histopathology diagnosis was ovarian mucinous cystadenoma1. The authors emphasized the rarity of concomitat pregnancy and ovarian cyst, and 15% of these mucinous cysts are malignant1. Huge ovarian cysts are more often benign, and less frequently they are diagnosed in association with normal pregnancies1. Major concerns in this setting should be the early diagnosis, close follow-up of the cyst growing, and appropriate intervention1. Interestingly, in the case herein commented the ovarian cyst was not detected by USG in the first two trimesters of pregnancy.
Keywords: Giant, cystadenoma, ovary.